2016
DOI: 10.1371/journal.pone.0156721
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychiatric Effects of STN versus GPi Deep Brain Stimulation in Parkinson's Disease: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundDeep brain stimulation (DBS) of either the subthalamic nucleus (STN) or the globus pallidus interna (GPi) can reduce motor symptoms in patients with Parkinson’s disease (PD) and improve their quality of life. However, the effects of STN DBS and GPi DBS on cognitive functions and their psychiatric effects remain controversial. The present meta-analysis was therefore performed to clarify these issues.MethodsWe searched the PUBMED, EMBASE, and the Cochrane Central Register of Controlled Trials databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
3
50
0
Order By: Relevance
“…Decline in verbal fluency has previously been reported following STN DBS and globus pallidus internus DBS in patients with Parkinson's disease, which has been described in a rather comprehensive meta review. 46 Decline in verbal fluency has also been reported after VIM DBS in ET, as mentioned previously. 14,16,33,44 So far there is no consensus as to what causes this deterioration.…”
Section: Discussionsupporting
confidence: 52%
“…Decline in verbal fluency has previously been reported following STN DBS and globus pallidus internus DBS in patients with Parkinson's disease, which has been described in a rather comprehensive meta review. 46 Decline in verbal fluency has also been reported after VIM DBS in ET, as mentioned previously. 14,16,33,44 So far there is no consensus as to what causes this deterioration.…”
Section: Discussionsupporting
confidence: 52%
“…Svenningsson et al, 2012;Duncan et al, 2014;Manza et al, 2017). Medical treatments fail to improve cognitive symptoms in many patients (Svenningsson et al, 2012), and cognitive outcomes following conventional high-frequency DBS are mixed (Okun et al, 2009;Combs et al, 2015;Wang et al, 2016), with a recent meta-analysis finding that STN-DBS patients experienced decrements in multiple cognitive domains compared to medically-treated controls (Cernera et al, 2019). Ideally, nextgeneration therapies would address both motor and cognitive aspects of the disease, but will likely require alternative patterns of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As for effects of DBS on cognitive outcomes, a recent meta-analyses of randomized controlled trials [167] showed that STN stimulation, as compared to internal pallidal stimulation (GPi DBS), was associated with subtle declines predominantly in attention, working memory and processing speed, phonemic fluency and learning, and memory; however, there were no significant differences in terms of quality of life. A systematic review and meta-analysis [168] demonstrated decreased performance only in the Stroop color-naming test in the STN DBS vs. GPi DBS.…”
Section: Treatmentmentioning
confidence: 99%